A Comparative Analysis of Consumer Protection Norms in E-Commerce Between Indonesia’s Civil Law and Singapore’s Common Law Systems - Agus Satory; Luis Santos; Samantha Gonzales (Rechtsnormen: Journal of Law, 2025)
Background. The rapid expansion of e-commerce has intensified consumer protection challenges in digital markets. Legal systems are required to respond to issues such as information asymmetry, unfair contract terms, and limited access to remedies, particularly within cross-border online transactions. Purpose. This study aims to analyze and compare consumer protection norms in e-commerce within Indonesia’s civil law system and Singapore’s common law system, focusing on how legal tradition shapes regulatory design and enforcement mechanisms. Method. The research employs a qualitative comparative legal approach using doctrinal and normative analysis. Primary legal sources, including statutes, regulations, and judicial decisions, are examined alongside secondary legal literature through a structured comparative framework. Results. The findings reveal that Indonesia emphasizes codified rules and administrative enforcement to ensure legal certainty, while Singapore relies on judicial interpretation and principle-based regulation to maintain flexibility. Conclusion. The study concludes that legal tradition remains a decisive factor in shaping consumer protection norms in e-commerce. The novelty of this research lies in its contextual comparative analysis within Southeast Asia, demonstrating that digitalization does not eliminate legal diversity but reconfigures its expression in consumer protection law.